Global Research Trends on Factors Affecting Patient Satisfaction Levels in Hospital Inpatient Wards: A Bibliometric Analysis - Defi Afriyanti; M. Bakhriansyah; Rosihan Adhani; Eko Suhartono; Syamsul Arifin (Malahayati Nursing Journal, 2024)
ABSTRACT Research on patient satisfaction in hospital inpatient rooms is one of the main focuses in efforts to improve the quality of health services. Understanding the factors that influence patient satisfaction is crucial for policy makers and healthcare practitioners. Although various studies have been conducted, the global map of this research trend is still not clearly depicted. This study aims to fill this gap by conducting a bibliometric analysis of the literature related to patient satisfaction in hospitals, using a visualization approach to provide deeper insights into the dynamics of research in this area. The method used involved data collection of scholarly articles from 2014 to 2024 using Google Scholar's Publish or Perish application. A total of 50 articles were selected based on relevance to keywords such as Patient Satisfaction, Inpatient Room, Satisfaction Factors, Hospital, and Health Services. This data was then analyzed using VOSviewer to visualize the relationship between various elements in the literature through network visualization, overlay visualization, and density visualization. This approach mapped research trends, identified key clusters, and showed collaboration patterns and dominant topics. The results show that service quality and patient satisfaction are the main focus in the literature. Research clusters showed significant attention to basic aspects of healthcare such as hospital care and facilities, while demographic aspects and specific determinants were less explored. Citation analysis showed that articles providing comprehensive reviews or practical models received more attention. In addition, the density visualization revealed the dominance of quality of care aspects, but also showed the potential for further research on topics such as technological innovation and the impact of health policy. The conclusions of this study show that although much research has been conducted, there are still significant research gaps that can be further explored. This study maps global trends in patient satisfaction studies, and provides guidance for researchers to focus on less explored areas, thereby contributing to the improvement of healthcare quality in hospitals. Keywords: Patient Satisfaction, Service Quality, Hospital, Bibliometric Analysis.